Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) terhadap Hasil Belajar IPS Siswa Kelas V Sekolah Dasar Se-Gugus II Kecamatan Panjatan Kulon Progo - Nur Asfatul Jannah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Abstract: The objectives of the study descriptively are to know (1) the category of learning achievement of social science subject that the teaching used STAD and (2) the category of learning achievement of social science subject that the teaching conventional, while the objective of the study comparatively is to know the difference of learning achievement of social science subject that was taught by using STAD and conventional teaching method. The type of the study was pre experimental design. Data collection data used documentation and test. Data analysis techniques used descriptive analysis and hypothesis testing used z-test that was started by homogeny variance test and normality test. This study shows that the results of analysis descriptively show that (1) the learning achievement of social science subject that the teaching used STAD was in fair category with the mean score 18.60 and (2) the category of learning achievement of social science subject using conventional with the mean score 16. Comparatively, the result of computation analysis shows that the score of zobs = 5.80 with the score of ztabie = 1.65, it means that there was difference very significant of learning achievement of social science subject that was taught by using STAD and conventional teaching method.